Experimental and Computational Fluid Dynamics Validation of Correlations for Dry Pressure Drop in Trays without Downcomer. Issue 3 (31st January 2020) - Brondani, Michel; Schlemmer, Diego Felipe; Cabral Wancura, João Henrique; Dias Mayer, Flávio; Hoffmann, Ronaldo; da Graça Rasteiro, Maria; Oliveira, Nuno M.; Gameiro Lopes, António M.
Abstract: The dry tray pressure drop (Δ P d ) is a design parameter that provides preliminary information about the total pressure drop. This work aimed to assess correlations for Δ P d prediction for different types of trays without downcomer and to evaluate the effects of the free area ratio ( φ ) and the hole diameter ( d ) on Δ P d . Assessment was performed by comparing results of several correlations with those from an experimentally validated computational fluid dynamics simulation. The study shows that the correlations of Červenka and Kolář, Bennett, Agrawal and Cook, and Stichlmair and Mersmann predicted the dry pressure drop satisfactorily. The correlation of Bennett, Agrawal and Cook can be recommended for the prediction of Δ P d for a wide range of geometries and operation conditions. Also, φ has a higher influence on Δ P d than d . Abstract : A computational fluid dynamics model for the dry pressure drop (Δ P d ) in trays without downcomer was developed and its experimental validation conducted. The results were compared with values predicted by different correlations. The conclusion was that the correlation by Bennett, Agrawal and Cook can predict Δ P d for a wide range of tray geometries and operation conditions.